IMPROVING STUDENTS’ SPEAKING ABILITY BY USING EXAMPLE NON-EXAMPLE TECHNIQUE AT SECOND GRADE OF STATE JUNIOR SCHOOL 1 LARANGAN PAMEKASAN - setiyawan, arisandi; Hanna, Ina Daril (Lingual Journal of Language and Culture; Vol 7 No 1 (2019): Lingual: Journal of Language and CultureDO - 10.24843/LJLC.2019.v07.i01.p03, 2019)
This study is a classroom action research (CAR). This study proposed example non example technique to teach English for second grade students at state junior high school 1 Larangan Pamekasan to solve the students’ problems on speaking skill. The result of the preliminary study indicated that the problem of the students toward their speaking skill is the average speaking score is lower than the minimum standard of learning (KKM). Based on the pre-test, the students who got score more or equals to 75 are 7 students and 33 students got less 75. Then the researchers collaborated with the teachers try to solve the problem using example non-example technique using classroom action approach. The results showed that the instruction through example non-example technique in the Cycle I and Cycle II, there was improvement of students’ speaking ability at second grade of state junior high school 1 Larangan Pamekasan. The students were more imaginative and feel free to show their understanding about the pictures. It made they motivate to learn and they could improve their speaking ability.